Problems and corrective measures of promoting the green construction of high-quality settlement buildings. Issue 1 (March 2020) - Huang, Mingqiang; Lin, Ruijuan; Wang, Weiwei; Song, Zixin; Xia, Xumei
Abstract: The green construction of high-quality settlement buildings is related to the people's life, the integrity of the government and social stability. Accelerating the construction of high-quality settlement buildings is helpful to promote the harmonious development of society. This study first expounds the significance of promoting the green construction of high-quality settlement buildings, then analyzes three major problems in the construction process of settlement buildings based on the data of previous research, and on this basis puts forward corresponding countermeasures and suggestions to promote the sustainable development of high-quality settlement buildings construction.